An integrative review on children's perceived and experienced subjective digital well-being - Holmarsdottir, Halla Björk; Seland, Idunn; Zinoveva, Liudmila; Barbovschi, Monica; Bărbuță, Alina; Parsanoglou, Dimitris; Symeonaki, Maria (Frontiers in Digital Health, 2025)
This review examines children's perceived and experienced subjective digital well-being by investigating their digital activities, behaviours and online relationships across three domains (Family, Leisure, and Education) presenting children's own perspectives. The included studies are limited to research published between 2011 and 2021 using European samples incorporating children aged 5–17 years. While research on children's digital well-being has expanded over the last two decades, the novelty of this review is that it presents research across all activity domains, representing an ecological approach to child development, one that aims to capture children's own views. The 23 studies identified for the review show, first, an apparent shortage of studies on children's well-being involving digital technologies that incorporate children's own perspectives on their situation. Second, the review shows that these studies relate primarily to well-being outcomes categorised as either social, emotional and cultural outcomes or as cognitive development and educational outcomes. Directions for further research on children's digital well-being are suggested.